ANALISIS POTENSI DAN KENDALA PENGEMBANGAN PEGADAIAN SYARIAH DI KOTA MEDAN - Randi Saputra; Kasyful Mahalli (Departemen Ekonomi Pembangunan USU, 2014)
This Skripsi aim to to know and explain any kind of strength and weakness and also opportunity and threat from pawnship office of Moslem law of exist in Field Town. By using analysis SWOT ( strength, weakness, opportunity and threat), hence will be able to be seen by that startegi of what will be taken for the meminimalisir of existing weakness and overcome the incoming threat to increase strength and take the opportunity - existing opportunity utilize to master the market compartment and huddle up all its client.This data used by is data of primary and sekunder. Primary data got from informan that is head of pawnship office of Moslem law as much 4 (four) of pawnship office of Moslem law which is gone the round of in Field town by direct interview and opened with the informan and give the kuesioner and also note the matter in this research. data Sekunder got by of the book, magazine, internet, other skripsi media and. Result of research indicate that the pawnship office of Moslem law be at the kuadran I that is strength and opportunity. This research is implication that pawnship office prospect existing Moslem law is fair Field town enough to to the fore its his.The result of analysis SWOT got by is difference of between strength and weakness of equal to 19 and difference of between opportunity and threat is equal to 13. Therefore result of from analysis of SWOT of pawnship office of Moslem law of Field town be at the Kuadran I ( positive - positive)/ progressive excellence by using strategy SO, that is by exploiting all strength to grab and exploit the opportunity of pawnship office of Moslem law of equal to- level of.Keyword: Potency, Constraint, Analyse the SWOT and Strategy.